Analysis of Gender-Based Violence in Malagasy urban areas: cases of Antananarivo 5th District and Morarano Toamasina - Raharijaona Sarindra; Randriamanantena Rakotoarisoa Jaqueline; Rabarison Arsène Andriatiana; Koto-te-Nyiwa Ngbolua (Britain International for Academic Research (BIAR) Publisher, 2025)
This study was conducted in the urban areas of Antananarivo 5 and Morarano, with the aim of examining the correlations between gender, education level, and the different forms of violence experienced by residents. A total of 500 participants, equally distributed between the two areas, were interviewed using a structured questionnaire. The results revealed a significant negative correlation between gender and education level, suggesting that a certain gender profile is associated with a lower level of education. Furthermore, education level showed moderate negative correlations with all forms of violence studied, indicating that a higher level of education could act as a protective factor against violence. The different types of violence were also interconnected, with psychological violence being positively correlated with physical, economic, and sexual violence.